Image Quality and Dose Assessment in Inner Ear Computed Tomography Imaging With a Flat Panel–Based System. Issue 2 (March 2015) - Brancaccio, Rosa; Bettuzzi, Matteo; Morigi, Maria Pia; Casali, Franco; Ragazzini, Luca
<x xml:space="preserve">Abstract</x> Purpose The temporal bone includes several important structures of the human body, some of which are smaller than 1 mm. The aim of this study is to demonstrate the feasibility of a computed tomography system capable of providing 3-dimensional images of the inner ear with low doses and a spatial resolution adequate for providing the surgeon with good guidance. Methods A laboratory prototype, based on a CMOS Hamamatsu model C10900D detector, was set up, and several tomographic tests were carried out on 2 dedicated phantoms. Results The proposed system is able to achieve a 150-μm spatial resolution (5% of modulation transfer function) with a voxel size of 88 μm, with an acceptable contrast and an estimated effective dose ranging from 1/20 up to 1/100 of the mean effective dose reported in literature for head computed tomography. Conclusion The new tomographic system has shown excellent characteristics and proves suitable for the imaging of the inner ear. In particular, this prototype requires very low radiation doses.